2022
DOI: 10.1097/md.0000000000029198
|View full text |Cite
|
Sign up to set email alerts
|

Expression of S100A9 and KL-6 in common interstitial lung diseases

Abstract: By evaluating S100 calcium binding protein A9 (S100A9) and Klebs von den Lungen-6 (KL-6) expression in patients with 4 common interstitial lung diseases (ILDs), we aimed to investigate whether S100A9 or KL-6 can be of any value in the differential diagnosis of these ILDs and simultaneously signal the disease progression. We collected the data of patients diagnosed with the 4 ILDs and underwent fiber-optic bronchoscopy and BAL in the First Affiliated Hospital, China Medical University from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…However, S100A9 levels in BAL fluid were positively correlated with KL-6 expression and the percentage of neutrophils in IPF patients and negatively correlated with lung function parameters and oxygen levels in SAR patients. The study concludes that measuring both KL-6 and S100A9 levels in BAL fluid can be useful for differential diagnosis of the four ILDs [25].…”
Section: Interstitial Lung Disease (Ild)mentioning
confidence: 84%
See 1 more Smart Citation
“…However, S100A9 levels in BAL fluid were positively correlated with KL-6 expression and the percentage of neutrophils in IPF patients and negatively correlated with lung function parameters and oxygen levels in SAR patients. The study concludes that measuring both KL-6 and S100A9 levels in BAL fluid can be useful for differential diagnosis of the four ILDs [25].…”
Section: Interstitial Lung Disease (Ild)mentioning
confidence: 84%
“…The study suggests that ILD is independently associated with increased FC levels in SSc [24]. Lin et al, [25] investigated whether S100A9 and Klebs von den Lungen-6 (KL-6) can be used as biomarkers for the differential diagnosis and disease progression of four common interstitial lung diseases (ILDs): idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonitis, connective tissue disease-associated ILD, and sarcoidosis (SAR). The study collected data from patients who underwent fiber-optic bronchoscopy and bronchoalveolar lavage (BAL) at a hospital in China between 2012 and 2020.…”
Section: Interstitial Lung Disease (Ild)mentioning
confidence: 99%
“…It has also been demonstrated that S1009A may promote atherosclerosis [ 36 ]. In an observational study by Lin et al [ 37 ], it was revealed that S100A9 levels were significantly elevated in BALF samples obtained from patients with severe IPF. It has also been demonstrated that S100A9 levels in the BALF of patients with IPF are positively correlated with the percentage of BALF neutrophils.…”
Section: Methodsmentioning
confidence: 99%
“…Krebs von den Lungen-6 (KL-6) is a mucin-1 glycoprotein encoded by the MUC1 gene [70]. It is normally expressed on type II pneumocytes in lung tissue.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…Serum KL-6 is thought to be produced by regenerating type II epithelial cells, with levels correlating to disease activity [71]. KL-6 also functions as a cell-surface barrier and should play a protective role associated with damage to the alveolar epithelial barrier molecule [70]. Notably, KL-6 levels have been reported to exhibit an inverse correlation with DLCO [49].…”
Section: Serum Biomarkersmentioning
confidence: 99%